Complex interplays between limpets and alien species in South Africa: multispecies interactions, zonation and size effects - Branch, George M.; Steffani, Nina; Pfaff, Maya C.; Baliwe, Ndiviwe G.; Zeeman, Zannè (Frontiers in Marine Science, 2023)
The effects of alien species differ among species. We integrate observations and experiments to tackle the progressive effects of three alien species – the mussels Mytilus galloprovincialis and Semimytilus patagonicus, and the barnacle Balanus glandula – on limpet species in South Africa. We describe four aspects: (1) Interactions among algae, the limpet Scutellastra granularis and M. galloprovincialis, deduced from a manipulative field experiment. (2) The influences of B. glandula on S. granularis and on Afrolittorina knysnaensis. (3) Documentation of how the zonation of S. granularis has been transformed by the successive arrival of these three aliens. (4) An assessment of how effective the published predictors of the effects of M. galloprovincialis have been when applied to S. patagonicus. We conclude: (a) S. granularis improves mussel survival and condition by regulating algae that would otherwise overgrow and choke the mussels. (b) B. glandula has largely occupied the upper half of rocky shores, and at high densities depletes or eliminates suitable bare-rock habitat for S. granularis. However, it has positive effects on another gastropod, A. knysnaensis. (c) M. galloprovincialis dominates the midshore and has positive effects on the recruitment of S. granularis, but its adults are negatively influenced. Thus, size composition, density, reproductive output and zonation are all altered by this mussel. (d) S. patagonicus presents different challenges to those created by M. galloprovincialis, settling at much greater densities, lower down the shore, and reaching smaller maximum sizes. Rather than generating a favourable habitat for epizootic S. granularis recruits and juveniles, it almost completely excludes that limpet. We conclude that the influences of alien species depend on the nature of the invader and complex interactions among species. Collectively, the three alien species now cover almost all zones on wave-exposed rocky shores, completing the ‘zonation squeeze’ on limpets, but are less influential on wave-sheltered shores and in years when recruitment is low.